1993
DOI: 10.1128/iai.61.3.1004-1015.1993
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli heat-labile toxin subunit B fusions with Streptococcus sobrinus antigens expressed by Salmonella typhimurium oral vaccine strains: importance of the linker for antigenicity and biological activities of the hybrid proteins

Abstract: A set of vectors possessing the genes for aspartate semialdehyde dehydrogenase (asd) and the B subunit of the heat-labile enterotoxin of Escherichia coli (LT-B) has been developed. These vectors allow operon or gene fusions of foreign gene epitopes at the C-terminal end of LT-B. Two groups of vectors have been constructed with and without leader sequences to facilitate placing of the foreign antigen in different cell compartments. Two Streptococcus sobrinus genes coding for principal colonization factors, surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…This strain induced the highest levels of B cell immunogenicity (Table 4 and Figures 2B, 3 and 4). This result is similar to those reported in previous studies, which have found that lowering the plasmid copy number results in enhanced plasmid stability and a reduction in the expression levels of heterologous antigens to non-toxic levels [31][32][33][34].…”
Section: B Cell Responses and Soluble Antigen Expression Levelssupporting
confidence: 92%
“…This strain induced the highest levels of B cell immunogenicity (Table 4 and Figures 2B, 3 and 4). This result is similar to those reported in previous studies, which have found that lowering the plasmid copy number results in enhanced plasmid stability and a reduction in the expression levels of heterologous antigens to non-toxic levels [31][32][33][34].…”
Section: B Cell Responses and Soluble Antigen Expression Levelssupporting
confidence: 92%
“…It is thought that TetC promotes the immune response against fused antigens by providing additional T cell helper epitopes [131]. In other studies, Streptococcus sobrinus antigens [132] or the E. coli heat-stable enterotoxin [133] were expressed in Salmonella as fusions to the E. coli heat-labile toxin subunit B (LT-B), which is also known to have immune-enhancing e¡ects. LT-B and CT-B, the cholera toxin B subunit, are well-known non-toxic adjuvants which contain structural features that provide adjuvant and immunogenic stimulation in the intestinal mucosa [134].…”
Section: Low Immunogenicitymentioning
confidence: 99%
“…It was also of interest to express multiple repeats of site D fused to LT-B to increase the immunogenicity of this epitope. Two synthetic complementary oligonucleotides encoding residues 371-400 of TGEV S protein, corresponding to site D sequence, were hybridized, cloned into the asd + LT-B expression plasmid pYA3048 (asd + LT-B +) (Jagusztyn-Krynicka et al, 1993), and electroporated into the restriction negative, modification positive strain S. typhimurium hsdLT hsdSA hsdSB Aasd Z3730 (pYA232) . The vector:insert ratio used in the ligation was 1:10 in order to obtain a collection of recombinant plasmids in which the LT-B genes were fused to a variable number of sequences of site D combined in the two possible orientations.…”
Section: Animal Bmentioning
confidence: 99%
“…The nucleotide sequence of site D that was cloned (5'-ATCTCCT-GTTACACCGTTTCCGACTCCTCCTTCTTCT-CCTACGGTGAAATCCCGTTCGGTGTTAC-CGACGGTCCGCGTTACTGCTACGTT-3') was not exactly the same as that of the S gene from TGEV genome, since some triplets present in the viral sequence were substituted for other synonymous triplets of high frequency of use in Enterobacteriaceae. The fusion of site D sequence to LT-B was done to the carboxyl end of this molecule through a linker coding for 6 amino acids containing two prolines, in order to preserve the molecular properties of LT-B, such as pentamerization and GM1 binding (Jagusztyn- Krynicka et al, 1993).…”
Section: Animal Bmentioning
confidence: 99%
See 1 more Smart Citation